Institutional Challenges In Managing County Government Resources In Kenya - ORIBU, WILLIAM SAGINI (Archives of Business Research, 2020)
In 2010 the Government of Kenya promulgated a new Constitution, articulating a devolved-system of Government entailing a National Government and County Governments. As a key pillar to the constitution of Kenya, devolution seeks to bring governance closer to the people. Kenyans are therefore looking at the county governments to derive the required change in the country. However, fundamental challenges have continued to dog the Counties including irregular or delayed disbursement of devolved funds from the national Exchequer; low revenue collection levels from local sources; weak and uncoordinated planning and execution among others. This has led to several stalled projects; indebtedness to suppliers; inadequate capacity at the county level to effectively and efficiently perform the devolved functions; inadequate financial resources among others. Although there are opportunities for Foreign Direct Investment and capital inflow; Public-Private Partnerships; Grants; Exchange programs; and wider markets for the local products, that the Counties need to explore and pursue, most of them are not in a position to sustain themselves. The purpose of this paper is to review the Institutional and Legal frameworks as provided by the Constitution of Kenya using the business sustainability model of the seven Ps (i.e. Preparation, People, Processes, Preservation, Place, Product and Production). It is hoped that the paper will form a conceptual framework to inform future county Government’s strategic decisions in order to utilize grants from development partners for the improvement of their citizens welfare. Further the paper will inform policy makers and development partners on fundamental areas that may need to be looked at in order to ensure effective utilization of available resources.